The Effect of Speos Method on Increasing Breast Milk among Mother with Post Section Caesaria in Pelni Hospital, Jakarta - Ety Nurhayati (International Journal of Nursing and Health Services (IJNHS), 2020)
In Jakarta, the proportion of low birth weight is 6.0%. LBW has difficulty adapting to extra-uterine life. This is due to the organ systems' inability, such as the lungs, heart, kidneys, liver, and digestive system. The SPEOS method can be used to increase breast milk production in mothers. This study aims to identify whether there is an effect of the SPEOS method on the increase in breast milk production in post-section caesarian mothers at Pelni Hospital, Jakarta. The sample used was Post-Caesaria Section Patients with 64 respondents. The method used was a quasi-experiment with a pre-test and post-test control group design approach. The statistical test used was the paired-sample t-test, so breast milk production was p-value <0.05. This shows a significant effect between the SPOES method on the increase in milk production in post-section caesarian mothers at Pelni Hospital, Jakarta. It is suggested that PELNI Hospital Jakarta need to implement a new policy so that breast milk production increases with the SPEOS method in Post Sectio patients